Social, biological, and programmatic factors linking adolescent pregnancy and early childhood undernutrition: A path analysis of India's 2016 National Family and Health Survey - Nguyen, Phuong Hong; Scott, Samuel P.; Neupane, Sumanta; Tran, Lan Mai; Menon, Purnima (Elsevier, 2019)
Adolescent pregnancy and child undernutrition are major social and public health concerns. We aimed to examine associations between adolescent pregnancy and child undernutrition in India, where one in five adolescents live, and one in three of the world's stunted children.